2008
DOI: 10.1093/annonc/mdn392
|View full text |Cite
|
Sign up to set email alerts
|

CD5 expression is potentially predictive of poor outcome among biomarkers in patients with diffuse large B-cell lymphoma receiving rituximab plus CHOP therapy

Abstract: CD5 expression was the only significant prognostic factor among the biomarkers examined in this study. Further studies with larger numbers are warranted to confirm the prognostic significance of CD5 expression for patients with DLBCL receiving rituximab-containing chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
1
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 23 publications
8
86
1
7
Order By: Relevance
“…These results are in agreement with the recent study looking at the outcome of CD5 ϩ DLBCL where 90% of CD5 ϩ biopsies were also Bcl-2 protein positive. 21 Although CD5 ϩ is associated with clinical outcome, our Cox regression analysis suggests that discordant CD20 or high-risk clinical features, not CD5 ϩ , is the main contributor of the negative prognostic effect of CD5 ϩ DLBCL. Another possibility is that discordant CD20 may be surrogate marker for cells that are "frozen" at a different stage of differentiation reflected by a slightly higher proportion of ABC subtypes in the discordant CD20 group.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These results are in agreement with the recent study looking at the outcome of CD5 ϩ DLBCL where 90% of CD5 ϩ biopsies were also Bcl-2 protein positive. 21 Although CD5 ϩ is associated with clinical outcome, our Cox regression analysis suggests that discordant CD20 or high-risk clinical features, not CD5 ϩ , is the main contributor of the negative prognostic effect of CD5 ϩ DLBCL. Another possibility is that discordant CD20 may be surrogate marker for cells that are "frozen" at a different stage of differentiation reflected by a slightly higher proportion of ABC subtypes in the discordant CD20 group.…”
Section: Discussionmentioning
confidence: 73%
“…19 Given that CD5 ϩ DLBCL has been previously shown to be associated with an inferior survival in CHOPand more recently in R-CHOP-treated patients, we determined the association of CD5 coexpression on B cells with clinical outcome. 20,21 Indeed, CD5 ϩ DLBCL was associated with an inferior survival in both CHOP-and R-CHOP-treated patients (P ϭ .008 and P ϭ .008, respectively; Figure 4). Similar to the discordant CD20 group, these patients also presented with advanced-stage disease and higher IPI scores, but unlike previous reports, this was predominantly seen in older men.…”
Section: Discordant Cd20 Expression Is Associated With Cd5 Expressionmentioning
confidence: 97%
“…The prognosis of de novo CD5 + DLBCL is poor in cases treated with CHOP therapy and is suggested to remain poor even after treatment with rituximab (Yamaguchi et al 2002;Ennishi et al 2008). CD5 antigen is expressed in the majority of SLLs and MCLs and in 9.8% of DLBCLs (Taniguchi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In another study of systemic DLBCL excluding PCNSL, Ennishi et al reported that 11 from 121 cases (9%) were revealed as CD5-positive by flow cytometry, whereas only 7 (6%) cases showed positive staining for CD5 (4C7, Novocastra) immunohistochemically. 22 Ennishi et al pointed out that CD5 paraffin immunohistochemistry is less sensitive and they concluded that flow cytometric analysis or frozensection immunohistochemistry needs to be carried out for the detection of CD5 in DLBCL. We consider that the very low proportion of CD5-positive cases in this study arose from these methodological conditions.…”
Section: Discussionmentioning
confidence: 99%